(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The purpose of the study was to determine the Implementation of the School Mover Program in Improving the Quality of Independent Learning Education at UPT SD Negeri 114 Pinrang Regency. The type of research that uses a qualitative method with a descriptive research type, data collection techniques through observation, interviews, and documentation, The results of the study indicate that the communication process in the implementation of the school mover program policy at UPT SD Negeri 114 Pinrang Regency has been effective where communication can be in formal form through official letters and face-to-face meetings. In addition, the availability of resources, namely educators, physical facilities, and technology, have been well managed to support the School Mover and Independent Learning Programs. Implementer disposition Support from the principal, teacher adaptation to innovative methods, and positive student responses to interactive and collaborative learning. The bureaucratic structure plays a role in supporting the implementation of the School Mover Program through technical guidance, training, funding, and monitoring and evaluation.